Analysis Of Digital Cooperation And Promotion Network Strategy To Improve Marketing Performance Of Anakraja Waterpark & Resort - Rina Fitriana; Abi Sapta Dinata; Mita Purnamasari (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
The growth of the Indonesian tourism industry has created increasingly fierce competition for hospitality businesses, including family recreation resorts. This situation demands that businesses implement integrated marketing strategies that utilize digital channels and build collaborative networks. This study aims to describe the collaborative network implemented by Anakraja Waterpark and Resort, analyze the digital promotion strategies implemented across various media channels, and evaluate the contribution of this integration to the resort's marketing performance. The study employed a descriptive qualitative approach through interviews, observations, and documentation analysis, analyzed using the Miles, Huberman, and Saldaña model. The results indicate that Anakraja's collaborative network is still limited to a single online booking platform and situational collaborations with local travel agents, resulting in suboptimal marketing reach. Digital promotion strategies have been actively implemented through Instagram and TikTok, but are not supported by structured content planning, visual identity, or performance evaluation. The integration between the collaborative network and digital promotion has not been effective, resulting in a significant impact on increasing occupancy rates and stabilizing demand. The study concludes that Anakraja's marketing effectiveness requires diversification of partnerships and strengthening of a digital strategy designed in an integrated manner to create more equitable and sustainable marketing growth.